2016
DOI: 10.1364/josaa.33.001523
|View full text |Cite
|
Sign up to set email alerts
|

Symmetric form-invariant dual Pearcey beams

Abstract: We introduce another type of Pearcey beam, namely, dual Pearcey (DP) beams, based on the Pearcey function of catastrophe theory. DP beams are experimentally generated by applying Fresnel diffraction of bright elliptic rings. Form-invariant Bessel distribution beams can be regarded as a special case of DP beams. Subsequently, the basic propagation characteristics of DP beams are identified. DP beams are the result of the interference of two half DP beams instead of two classical Pearcey beams. Moreover, we also… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(25 citation statements)
references
References 20 publications
0
25
0
Order By: Relevance
“…Examples of higher singularities that have been studied experimentally are the parabolic and symbolic and X 9 catastrophes in light focused by water drops [45], and sections of the butterfly catastrophe in optical beams [8]. In addition, paraxial beams whose cross-sections contain four [46] or five [47] cusps have been created, though not interpreted as unfoldings of higher catastrophes. The most conceptually far-reaching example of this kind concerns the fluctuations of random short waves, which are predicted [48,49] to depend on the full hierarchy of singularities.…”
Section: Discussionmentioning
confidence: 99%
“…Examples of higher singularities that have been studied experimentally are the parabolic and symbolic and X 9 catastrophes in light focused by water drops [45], and sections of the butterfly catastrophe in optical beams [8]. In addition, paraxial beams whose cross-sections contain four [46] or five [47] cusps have been created, though not interpreted as unfoldings of higher catastrophes. The most conceptually far-reaching example of this kind concerns the fluctuations of random short waves, which are predicted [48,49] to depend on the full hierarchy of singularities.…”
Section: Discussionmentioning
confidence: 99%
“…Equations ( 3) and ( 4) can be calculated numerically in the method of contour rotation on the complex s plane as s → s ′ e i ∕8 , which ensures the convergence of the integral while s ′ → ±∞. [28] Therefore, under paraxial approximation, the propagation expressions of RPOPGBs in xand y-directions in free space can be obtained by Fresnel diffraction integral formulas: [28] E…”
Section: Analytic Solution Of the Rpopgbs In Free Spacementioning
confidence: 99%
“…[25] In 2014, a virtual source to generate Pearcey beams was demonstrated by Deng et al [26] In 2015, Kovalev et al [27] generated and introduced a family of form-invariant half-Pearcey beams (HP-beams). In 2016, it was reported that, based on the Fresnel diffraction catastrophes, dual Pearcey beams (DP beams) were successfully obtained by interfering a pair of half DP beams, [28] and the form-invariant Bessel beams were experimentally confirmed as particular forms of DP beams. As Pearcey beams have been intensively investigated recently, their paraxial and non-paraxial propagation properties are increasingly reported.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the characteristic of self-acceleration [9], Airy beams propagates along a quadratic trajectory on the transverse plane, and the main lobe remains basically unchanged. The sudden autofocus ability of a circular Airy beams in a linear region has been theorized and experimentally demonstrated [10][11][12]. This characteristic can be used to improve the performance of optical tweezers.…”
Section: Introductionmentioning
confidence: 99%